Response control of a large transmission tower-line system under seismic excitations using friction dampers. Issue 8 (August 2017) - Chen, Bo; Weng, Shun; Zhi, Lunhai; Li, Dongming
The transmission tower-line system is widely used in electric infrastructures across the world and generally possesses a small stiffness and low structural damping. The excessive vibration of a transmission tower-line system subjected to seismic excitations may induce a structural damage or failure. To avoid the excessive vibration under strong earthquakes, a large transmission tower-line system requires some measures to abate their dynamic responses. Friction damper is a solution to realize the response control of a transmission tower-line system. In this regard, the response mitigation and performance assessment on a transmission tower-line system with friction dampers under strong earthquakes are actively carried out in this study. The analytical model of a transmission line is proposed based on Hamilton's variational statement of dynamics and Lagrange's formulation. A two-dimensional lumped mass model of a transmission tower is developed for the dynamic analysis by simplifying the three-dimensional finite element model. The mechanical model of a friction damper is established by considering the effect of damper axial stiffness. The equations of motion and dynamic analytical method of a transmission tower-line system without/with friction dampers subjected to seismic excitations are proposed. In addition, the approach for assessing energy responses of a transmission tower-line system without/with friction dampers subjected to seismic excitations is also developed. A real transmission tower-line system is taken as an example to examine the feasibility of the proposed control approach. The parametric study is conducted to investigate the effects of damper control force, damper stiffness, earthquake intensity, and damper location. The made observations demonstrate that the implementation of friction dampers in a transmission tower-line system can substantially suppress the seismic responses with optimal damper parameters.